Evaluación de doce variedades de caña de azúcar en la zona alta del valle Chicama por tres cortes consecutivos planta, soca uno y soca dos, 2018 - Camus Davila, Odar (2019)
ABSTRACT There is no doubt that the sugar industry is constituted as one of the most important in the world; because the multiple benefits it provides are daily and unavoidable consumption by the entire world population; so all research aimed at improving production and productivity is welcome. This research was based on the comparative study of 12 varieties of sugar cane, in the Atahualpa I field, belonging to the Sausal Annex, Rome Division, Casa Grande, using the same agronomic management of the fields commercially. A randomized complete block design (DBCA) was used, with 4 repetitions and 12 treatments in 48 plots that covered 10.30 has of experimental area. This method of regional testing is used in different countries with different types and numbers of varieties according to the needs and requirements of the sugar industry subject to different agroecological sites, obtaining a ranking of varieties according to the evaluated requirement, taking into account the indicators of field management. To obtain the database, 3 consecutive cuts were considered: plant, soca 1 and soca 2 and the following indicators were considered: ton cane per hectare (tch), ton cane per hectare month (tchm), ton of sugar per hectare (tah) ) tons of sugar per hectare month (tahm), sucrose (% sac) and bags of sugar per hectare (bls az / ha); to which the analysis of variance was applied with the Duncan test to determine the ranges or sub sets of the indicators found and in blocks to verify if the conditions of the study of the blocks are homogeneous; results that served to validate and determine the most profitable varieties. According to the data finding weighted from 1 to 12 where 12 is the maximum and 1 is the minimum value. Obtaining as a result the variety RB72-454 reached the maximum weighting (tch, tchm, tah, tahm,% sac, bls az / ha) and the varieties H57-5174, RB83-5054 and RB83-5486 with weighting of the indicators evaluated by above the average and H32-8560 with the minimum weighting. Likewise the average of the 3 cuts indicates that the variety RB72-454 with weighted of Sucrose of 6 and tons per hectare of 11 has greater number of bags of sugar per hectare and the variety H57-5174 with higher weighted of tons per hectare 12 and weighted saccharose 1 has the second best result, it is concluded that tons per hectare has a greater impact than sucrose on the number of bags of sugar produced per hectare.